Analisis Pengaruh ROA, DER, PER, Dan EVA Terhadap Return Saham Pada Perusahaan Food And Beverage - Namira Ufrida Rahmi; Gladys Callista; Silvya Wijaya; Melly Melly; Tiffany Tiffany (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Investment or what we often call investment is an investment activity in the form of assets or funds by a company or individual with the aim of getting profits in the future. Investment is also a factor to increase economic growth. Investments can be made in the capital market which is a place where investors and companies seeking funding sources meet. The hope for investors who invest their funds in a company is to get a maximum return in the future. This study aims to determine and analyze Return of Assets, Debt to Equity Ratio, Price Earning Ratio and Economic Value Added to Stock Returns in food and beverage companies listed on the Indonesian stock exchange in 2017 - 2019. The research approach used in this study is quantitative approach. With the purposive sampling method, a sample of 15 food and beverage companies listed on the Indonesian stock exchange in 2017 – 2019, multiplied by three years of research. The type of data used in this research is secondary data. Secondary data is the financial statements of food and beverage companies listed on the Indonesia stock exchange in 2017 – 2019 with the website www.idx.co.id. The results show that Return of Assets, Debt to Equity Ratio, Price Earning Ratio, Economic Value Added have a simultaneous effect on Stock Returns in food and beverage companies listed on the Indonesian stock exchange in 2017 - 2019. Return on Assets has no effect and is not significantly significant. partial to Stock Returns in food and beverage companies listed on the Indonesian stock exchange in 2017–2019. Debt to Equity Ratio has no effect and is not partially significant to Stock Returns in food and beverage companies listed on the Indonesian stock exchange in 2017–2019. Price Earning Ratio has partial and insignificant effect on Stock Return in food and beverage companies listed on the Indonesian stock exchange in 2017 – 2019. 4.Economic Value Added has partial and significant effect on Stock Return in food and beverage companies listed on the stock exchange Indonesian securities in 2017 – 2019. Keywords: Return of Assets, Debt to Equity Ratio, Price Earning Ratio, Economic Value Added and Stock Return.